God and Mrs Thatcher: A Review Article. Issue 1 (January 2016) - Percy, Martyn
Abstract : This article summarises the argument of the book under review, namely that Margaret Thatcher intended to create a Christian Britain characterised by the piety and thrift of her father, but in fact produced a secular individualistic country worshipping consumer capitalism. Accepting this analysis as accurate, the reviewer demonstrates how the Church of England has followed the shift to right, with the social gospel that produced Faith in the City giving way to an acquisitive church obsessed with 'the metrics of success'.